The Description of Elderly Social Interaction during COVID-19 Pandemic in Nursing Home of Jember - Bela Aprilia Nuraini; Latifa Aini Susumaningrum; Tantut Susanto; Hanny Rasni; Fahruddin Kurdi (Nursing and Health Sciences Journal (NHSJ), 2021)
COVID-19 pandemic has been restricting the physical and social interaction among elders. Furthermore, this pandemic has been limiting elders’ participation in their social environment. This research aimed to analyze the implementation of social interaction among elders during the COVID-19 pandemic at the Nursing Home of Jember. The method used in this study was descriptive research with a cross-sectional approach. The sample used in this study was 74 elders at the Nursing Home of Jember which matched with the criteria of research inclusion and exclusion. The data analyzed was the social interaction which was used to find out the adaptation of elders’ social interaction during the pandemic. The one-sample Kolmogorov-Smirnov's test was used to reach the aim of this study. The result showed that social interaction among elders underwent a significant change during the pandemic Md(P25-75)=11(9-14); Z=0,104; p-value 0,045. It can be concluded that there was a significant change in elders’ social interaction during the COVID-19 pandemic. Therefore, discussing and telling are activities that needed to implement for improving the social interaction among elders during the pandemic.